(untitled) (Journal of Parents and Teachers, 2014)
Having a student with cerebral palsy at school means facing several difficulties in different areas: in the student’s social-affective field, adapted or non-adapted infrastructures in context, objects with low utility, organization of activities and even teachers. This article gives answers to all these difficulties.